FANTASTIC FUNGI AROUND US: A CASE STUDY OF IPB UNIVERSITY CAMPUS FOREST - Ivan Permana Putra; Mega Putri Amelya; Septina Veronica; Muhammad Sholeh Kurnianto (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
Campus forest is the area of education and conservation at IPB University. The preliminary study proved that the area stores high biodiversity, including macroscopic fungi, which have not been well recorded. This study aimed to inventory the diversity of macroscopic fungi in the IPB University campus forest (IPBUCF) to be used as media for mycology course practice and optimize the future's mushroom potential. The results showed 18 mushroom species divided into two divisions, namely Basidiomycota and Ascomycota. Basidiomycota consist of: Agaricus sp., Amanita sp., Amauroderma sp., Conocybe sp., Crinipellis sp., Gymnopus sp., Hypholoma sp., Marasmius sp.1, Marasmius sp.2, Naucoria sp., Pluteus sp. 1, Pluteus sp. 2, Pholiota sp., Ramaria sp., Rigidoporus sp., and Russula sp. Ascomycota members were divided into two classes, namely Pezizomycetes and Eurotiomycetes. The identification results confirmed the existence of Cookeina cf. tricholoma and Onygena sp. In this paper, we explained how to describe mushrooms for identification using macroscopic features.